Estrogen- and stress-induced DNA damage in breast cancer and chemoprevention with dietary flavonoid. (December 2017) - Yasuda, Michiko; Sakakibara, Hiroyuki; Shimoi, Kayoko
Abstract Breast cancer is one of the most commonly diagnosed female cancers and a leading cause of cancer-related death in women. Multiple factors are responsible for breast cancer and heritable factors have received much attention. DNA damage in breast cancer is induced by prolonged exposure to estrogens, such as 17β-estradiol, daily social/psychological stressors, and environmental chemicals such as polycyclic aromatic hydrocarbons (PAHs) and heterocyclic amines (HCAs). DNA damage induced by estrogen and stress is an important factor in the pathogenesis and development of breast cancer and is now recognized as a critical provision for chemoprevention of breast cancer. In this review, we summarize the relationships between estrogen- and stress-induced DNA damage with regard to the pathogenesis and development of breast cancer. We also discuss recent investigations into chemoprevention using dietary flavonoids such as quercetin and isoflavones.